Improving the Reading Comprehension of Grade III Learners through the Use of Story Maps - Cabangon, Jazztine Anne L.; Ignacio, Rachelle Ann D. (Asian Journal of Applied Education (AJAE), 2025)
Reading comprehension plays a vital role in a child’s cognitive growth, helping them gain knowledge and build mental skills. This study explored how using story maps could improve the reading comprehension of Grade III learners in an online class setting. A pre-experimental one-group pretest-posttest design was used to measure changes before and after the intervention. The study involved quantitative data collection, analyzed using the Paired Sample T-test through SPSS software. Results showed a significant improvement in learners’ reading comprehension after using story maps. These findings suggest that story mapping is an effective tool for enhancing comprehension skills, and it may be a valuable strategy for teachers conducting online classes with young learners.